PENERAPAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD SWASTA PONDOK 4 INDRIPLANT PERANAP KABUPATEN INDRAGIRI HULU - Syarifah Emilyah; Jesi Alexander Alim; Mahmud Alpusahri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The learning activities in private primary schools cottage 4 Indriplant of Peranap need for improving student learning outcomes, by seeking active students in learning and students are also expected to be able to do the work ultimately to be able to achieve the specified KKM school, but the students' learning outcomes class IV Math Private cottage 4 Indriplant of Peranap very low, there are still students who have not yet reached the standard KKM. Judging from the 24 students who reach KKM only 16 people or 66.7% in the classical style. For that conducted the research study with the application of Indonesian Realistic Mathematics Education Approach (PMRI). This study aims to determine students' learning outcome class IV math Private cottage 4 Indriplant, by applying the approach of Indonesian Realistic Mathematics Education (PMRI). This research was conducted in the class IV Math Private cottage 4 Indriplant, in March even semester academic year 2014/2015 the number of students 24 people composed of 15 female students and 9 boys. The data collected in the form of the observation of the activities of teachers and students as well as students' test results. The results showed that the activity of teachers has increased In the first cycle the average percentage of the activity of teachers is 70% with good category while in the second cycle increased to 90% to the category of Very Good, analyzed the increased activity of teachers is 20%. For student activity also increased, in the first cycle the average percentage of student activity that is 70.75% with good category while in the second cycle increased to 88.85% with the category of Very Good, analyzed the increased activity of students is 18.1%. For improving student learning outcomes in terms of the percentage of classical completeness in each cycle. For a basic score that is 66.7%, increase in the first cycle to 83.3%, and the second cycle increased to 100%, meaning that overall the student has reached the minimum completeness criteria. Thus the application of Indonesian Realistic Mathematics Education Approach (PMRI) can improves the learning outcomes of class IV math student Private cottage 4 Indriplant Peranap academic year 2014/2015.Keywords : Indonesian Realistic Mathematics Education (PMRI), Mathematics Learning Outcomes